Conditions of diffusion of competitiveness clusters' technologies: A brief theoretical note. - Bi Goli Jean Jacques Iritié (International Journal of Economics and Finance, 2015)
Competitiveness clusters (or innovation clusters) are the focal point of French new industrial policy. They are based on classical cluster model and its well-known agglomeration positive externalities and on benefits of cooperation. After a brief literature review of cluster theory, we focus on the theoretical conditions under which French innovation clusters can foster production and diffusion of technological innovations. Our short critical analysis points out three non-exhaustive conditions: (i) the capacity to coordinate and to incitate cooperation in R&D; (ii) the capacity to favor production and technological knowledge transfer; (iii) the capacity to promote and to keep R&D appropriation by cooperating innovators.
Keywords: O20; O30; R30; 330; Innovation cluster; Coordination; R&D cooperation; Knowledge spillovers; Network externalities; Installed base; Absorptive capacity; Collective Appropriation